A New Hybrid Test Pattern Generator for Stuck-at –Fault and Path Delay Fault in Scan Based Bist - Karthikeyini, C; Anandhi, K (International Journal of Engineering and Technology, 2018)
Testing for delay and stuck-at faults needs a pattern of two checks and test sets square measure sometimes more. Built self-test (BIST) schemes square measure enticing for such comprehensive testing. The BIST check pattern generators (TPGs) for such testing ought to be designed accustomed guarantee high pattern-pair coverage. Within the planned work, necessary and decent conditions to complete/ supreme pattern-pair coverage for consecutive circuit has been derived. A replacement check data-compression theme that's a hybrid approach between external testing and inbuilt self-test (BIST) is analyzed. The planned approach is predicated on weighted pseudorandom testing and uses a unique approach for pressing and storing the load sets. Most existing check generation tools square measure either inefficient in mechanically characteristic the longest checkable methods thanks to the high process complexness or don't support at speed test mistreatment existing sensible design-for-testability structures, like scan style. During this work a check generation methodology for scan-based synchronous consecutive circuits is conferred, below 2 at-speed check methods employed in trade. The approach provides a balanced trade-off between accuracy and potency. Experimental results show promising runtime and fault coverage enhancements over existing ways.Â